Ciro Cardoso e a Economia Pré-Capitalista : traços de um intelectual sistematicamente polêmico - Frizzo de Moraes Lima, Fábio Afonso (Sociedades Precapitalistas.)
Along his academic career, Ciro Cardoso has worked on different areas of historical knowledge, from the futures in the Science Fiction to the remote past of Antiquity. Throughout the last 25 years of his life, Cardoso focused mostly on Ancient History and, to be more specific, on Egyptology. Regardless the conservatism of this field of knowledge, this paper shall demonstrate that Cardoso stoods out for his marxist militant view and kept as the axis of his work the denial of modernizing perspectives for the social structures of Antiquity, which ends up to naturalizes the capitalism as a human essence.